Next generation of biologics for the treatment of Crohn’s disease: an evidence-based review on ustekinumab - Jauregui-Amezaga, Aranzazu (Clin Exp Gastroenterol, 2017)
The limited efficacy of the currently available medical therapies in a proportion of patients with Crohn’s disease has led to the research and development of molecules that can block new inflammatory pathways. Ustekinumab is a fully human IgG1 monoclonal antibody which targets the common p40 subunit of the cytokines interleukin-12 as well as interleukin-23. Consequently, the Th1 and Th17 inflammatory responses are inhibited. Ustekinumab has been recently approved for its use in patients with Crohn’s disease. Its efficacy and safety was initially proved in patients with psoriasis and psoriatic arthritis. More recently, three Phase III trials have confirmed its efficacy in patients with Crohn’s disease refractory to anti-tumor necrosis factor therapy. This biologic agent appears safe, with no increased risk of infectious or malignant complications, and a low immunogenic profile.